COVID‐19 patients exhibit reduced procoagulant platelet responses. (6th October 2020) - Denorme, Frederik; Manne, Bhanu Kanth; Portier, Irina; Petrey, Aaron C.; Middleton, Elizabeth A.; Kile, Benjamin T.; Rondina, Matthew T.; Campbell, Robert A.
Abstract: Background: Emerging evidence implicates dysfunctional platelet responses in thrombotic complications in COVID‐19 patients. Platelets are important players in inflammation‐induced thrombosis. In particular, procoagulant platelets support thrombin generation and mediate thromboinflammation. Objectives: To examine if procoagulant platelet formation is altered in COVID‐19 patients and if procoagulant platelets contribute to pulmonary thrombosis. Patients/Methods: Healthy donors and COVID‐19 patients were recruited from the University of Utah Hospital System. Platelets were isolated and procoagulant platelet formation measured by annexin V binding as well as mitochondrial function were examined. We utilized mice lacking the ability to form procoagulant platelets (CypD plt−/− ) to examine the role of procoagulant platelets in pulmonary thrombosis. Results and Conclusions: We observed that platelets isolated from COVID‐19 patients had a reduced ability to become procoagulant compared to those from matched healthy donors, as evidenced by reduced mitochondrial depolarization and phosphatidylserine exposure following dual stimulation with thrombin and convulxin. To understand what impact reduced procoagulant platelet responses might have in vivo, we subjected mice with a platelet‐specific deletion of cyclophilin D, which are deficient in procoagulant platelet formation, to a model of pulmonary microvascular thrombosis. Mice with platelets lacking cyclophilin D died significantly faster from pulmonary microvascular thrombosis compared to littermate wild‐type controls. These results suggest dysregulated procoagulant platelet responses may contribute to thrombotic complications during SARS‐CoV‐2 infection.